IMPLEMENTASI PEMBELAJARAN BERBASIS NATURE OF SCIENCE (NOS) DALAM KURIKULUM IPA - Dinicen Viclara (Nusantara Hasana Journal, 2025)
This research aims to analyze the implementation of Nature of Science (NOS)-based learning in the Natural Sciences (IPA) curriculum through a Systematic Literature Review (SLR) approach. NOS is a learning approach that emphasizes students' understanding of the nature of science, including the processes, methods, and values underlying the development of scientific knowledge. Through a review of 30 research articles published between 2015 and 2023, it was found that the implementation of NOS in the science curriculum can enhance students' conceptual understanding, critical thinking skills, and scientific attitudes. However, challenges such as the lack of teacher training, limited resources, and misalignment with the national curriculum remain major obstacles. This study concludes that the integration of NOS into the science curriculum requires policy support, teacher training, and the development of relevant teaching materials